A systematic screen for tube morphogenesis and branching genes in the Drosophila tracheal system. - Amin S Ghabrial; Boaz P Levi; Mark A Krasnow (PLoS Genetics)
Many signaling proteins and transcription factors that induce and pattern organs have been identified, but relatively few of the downstream effectors that execute morphogenesis programs. Because such morphogenesis genes may function in many organs and developmental processes, mutations in them are expected to be pleiotropic and hence ignored or discarded in most standard genetic screens. Here we describe a systematic screen designed to identify all Drosophila third chromosome genes (∼40% of the genome) that function in development of the tracheal system, a tubular respiratory organ that provides a paradigm for branching morphogenesis. To identify potentially pleiotropic morphogenesis genes, the screen included analysis of marked clones of homozygous mutant tracheal cells in heterozygous animals, plus a secondary screen to exclude mutations in general "house-keeping" genes. From a collection including more than 5,000 lethal mutations, we identified 133 mutations representing ∼70 or more genes that subdivide the tracheal terminal branching program into six genetically separable steps, a previously established cell specification step plus five major morphogenesis and maturation steps: branching, growth, tubulogenesis, gas-filling, and maintenance. Molecular identification of 14 of the 70 genes demonstrates that they include six previously known tracheal genes, each with a novel function revealed by clonal analysis, and two well-known growth suppressors that establish an integral role for cell growth control in branching morphogenesis. The rest are new tracheal genes that function in morphogenesis and maturation, many through cytoskeletal and secretory pathways. The results suggest systematic genetic screens that include clonal analysis can elucidate the full organogenesis program and that over 200 patterning and morphogenesis genes are required to build even a relatively simple organ such as the Drosophila tracheal system.